Prospective Biomarker-Based Strategies for Early Diagnosis and Management of Periodontal Diseases: A Clinical Observational Study - Nadia Mansoor, Muhammad Ahmad, Uzma Tariq, Sadaf Raffi, Usman Mahmood, Humera Akhlaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Periodontal diseases are chronic inflammatory diseases of the supporting structures of teeth, leading to destruction and systemic associations. Historically the diagnostic methods have relied on clinical and radiographic techniques which reflect historical tissue destruction more so than active disease processes. Biomarker-based diagnostics are also poised to provide a promising avenue for early detection, disease monitoring as well as precision treatment strategies. Aims and objectives: This study aimed to evaluate the clinical relevance of salivary and gingival crevicular fluid (GCF) biomarkers in the diagnosis of periodontal diseases, monitoring disease progression, and treatment response. Methodology: A Clinical Observational Study was carried out from December 2020 to December 2022 considering sample size n=150 patients divided into healthy, gingivitis and periodontitis groups. At baseline, three months, and six months post-treatment periodontal parameters and levels of IL-1β, TNF-α, MMP-8, MMP-9, RANKL/OPG ratio, and 8-OHdG were measured. The associations of biomarkers with disease severity were determined by statistical analysis of ANOVA and correlation tests. Results: Biomarker levels were significantly elevated in gingivitis and periodontitis patients compared to healthy controls (p < 0.001). Post-treatment, inflammatory markers declined, but IL-1β, TNF-α, and 8-OHdG remained elevated in periodontitis, indicating persistent inflammation. The RANKL/OPG ratio remained high, suggesting continued bone resorption despite therapy. Strong correlations were observed between biomarkers and clinical parameters, reinforcing their diagnostic utility. Conclusion: Biomarker-based diagnostics provide an objective, real-time tool for periodontal disease detection and management. Their integration into routine periodontal assessment can enable early diagnosis, precision treatment, and improved long-term outcomes. Future research should focus on point-of-care biomarker assays and adjunctive host-modulation therapies to optimize periodontal care. Keywords: Periodontal disease, biomarkers, salivary diagnostics, inflammatory markers, bone resorption, early detection, precision periodontology, RANKL/OPG, periodontal therapy.